2021
DOI: 10.19080/artoaj.2021.26.556337
|View full text |Cite
|
Sign up to set email alerts
|

Use of GPS tracking collars on Sarda cattle in a Silvopastoral System

Marco Acciaro

Abstract: Free-roaming Sarda cows grazing a Mediterranean silvopastoral area were fitted with Global Positioning System (GPS) tracking collars to estimate daily distance travelled (DT), daily (DW) and maximum distance (DWM) to water, and proportion of time (PT) the cows were near the water source, in different seasons and physiological status (dry and lactating). From a herd of 12 cows grazing 54-ha pasture, characterised by deciduous oak wood and glades, three cows (N=3) were fitted with Knight GPS collar during four s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Moreover, in this season, the animals avoided the central area of the pasture, furthest from the fences, due to the high presence of bracken in this area. This confirms what was stated by Acciaro et al ( 28 ), who found that the shrub-encroached grassland areas were avoided in the summer, in conjunction with the maximum presence of bracken ( Pteridium aquilinum (L.) Kuhn), which are unpalatable species containing antinutritional factors ( 63 ). In autumn, the area with the highest probability of use was predicted to be in the northwest of the pasture, at higher elevation, likely characterized by slightly higher pasture quality compared to warmer areas where, in a Mediterranean environment, the grass is almost completely dry at that time.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, in this season, the animals avoided the central area of the pasture, furthest from the fences, due to the high presence of bracken in this area. This confirms what was stated by Acciaro et al ( 28 ), who found that the shrub-encroached grassland areas were avoided in the summer, in conjunction with the maximum presence of bracken ( Pteridium aquilinum (L.) Kuhn), which are unpalatable species containing antinutritional factors ( 63 ). In autumn, the area with the highest probability of use was predicted to be in the northwest of the pasture, at higher elevation, likely characterized by slightly higher pasture quality compared to warmer areas where, in a Mediterranean environment, the grass is almost completely dry at that time.…”
Section: Discussionsupporting
confidence: 89%
“…between the 2 years of study). The Sarda breed is a small-to-medium-sized local breed, well-adapted to the harsh environment of Sardinian hilly and mountainous areas ( 28 ) Supplemantary data sheet 1 . The stocking rate was held steady throughout the study duration in an attempt to avoid confounding stocking rate effects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation